Systemy zarządzania przez wartość - teoria i praktyka - Czarnecki, Maciej (Value based management systems - theory and practice, 2007)
VBM as a new trend, mainly in the fields of strategie management and corporate finance management, has become a freąuent topie of discussions in academic environment, as well as among managers and consultants. It impacts not only areas mentioned above, but all the areas of companies’ lives, including marketing, selling, motivation, goods storage etc. VBM systems are quite rarely implemented in real life as a comprehensive “system”, but morę and morę of them implement some of the “subsystems” of the VBM model. Morę than ever they reward employees based on their individual achievements, implement such tools as Balanced Score Card etc. VBM is not a “zero - one” phenomenon - in real corporate life it is not too easy to say the corporate is managed in linę with VBM or not. VBM surely madę an impact on corporate life, even though they do not always know about it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 338-348